«Les Sauvages» by J.-P. Rameau: a marketing ploy or an exercise in musical characterization? - Sukhlenko, Yurii (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study is to search for new perspectives on the phenomenon of programmability and characterization in the works of French harpsichord composers of the first third of the eighteenth century on the basis of one of the most popular miniatures by J.-P. Rameau «The Savages». In the research, the choice of the title is analyzed in connection with the principles of involvement of musical idioms of the time in the musical text to reproduce the exotic image, defined by the verbal program. The applied complex methodological approach allows us to find out the peculiarities of the reaction of Parisian salon musicians to the representatives of the nonEuropean «other» culture, which was presented by the delegation of North American Indians who visited Paris in 1725. The colorful images of «savages» could not go unnoticed by composers and music publishers, who, by titling musical works that evoked associations with exotic portraits of foreigners, increased the demand for their own musical products. Should we look for signs of crosscultural intersections only in the headline «inventions» or have recent impressions left their mark on musical texts? If so, to what extent did the existing «good taste» allow the composer and performer to authentically «copy» the exotic original? The search for answers to these questions is the main plot of this article. Main objective is to outline the specifics of the embodiment of the image of «savages» in music by prominent masters of European art, to comprehend the marketing prerequisites for creating a harpsichord piece in the context of this theme and the means of musical characterization of Indians proposed by J.-P. Rameau. The methodology consists of a comprehensive methodological approach that includes historical and contextual, biographical, comparative, genre and stylistic, and performance analysis methods. Results and conclusions. An overview of J.-P. Rameau’s compositional experience in reflecting Indians in music allows us to clearly separate the musical miniature «Les Sauvages» from other works of Indian music by his predecessors and contemporaries — it is the experience of direct acquaintance and the intention to «characterize» the exotic object of observation through the means of musical art. In «Les Sauvages», as in an early attempt at musical «characterization, » the composer did not try to literally imitate the original music of the native Americans. He used the musical vocabulary of his time, but, at the same time, he went beyond it, applying an emphatically extravagant, «savage» style of writing, undoubtedly brilliantly conveying the temperament of the performers of Indian dance on the stage of the Italian Theater in September 1725.